Increasing of Rice Yield by Using Growth Promoting Endophytic Bacteria from Swamp Land - Fitri, Siti Nurul Aidil; Gofar, Nuni (JOURNAL OF TROPICAL SOILS, 2010)
Increasing of Rice Yield by Using Growth Promoting Endophytic Bacteria from Swamp Land (SNA Fitri and N Gofar):  Swamp land has can be used as a paddy field that will be potential as a rice source However, this land has some limiting factors such as low fertility. On the other hand, continous used of inorganic fertilizer to improve soil fertility will also have some disadvantages. Therefore,  an alternative method as  fertilizers complement is needed.  Biofertilizer  is potential to be developed.  Previous research had succeeded to explore and selected some bacteria from rice tissues grown on swamp land.  That research had found two bacteria Consortium were named as Growth Promoting Endophytic Bacterial Consortium (GPEBC).  The aims of this research were (1) to evaluate the effect of a GPEBC population density and a level of N fertilizer on plant N absorption, and rice yield in the swamp soil, and (2) to find out the optimal population density of GPEBC and optimal dosage of N fertilizer on plant N absorption and rice yields in the swamp soil.  The research used a factorial completely randomized design with 3 factors and 3 replicates.  The first factor was a kind of GPEBC which consisted of Consortium A and consortium B.  The second factors was population density of GPEBC which consisted of 0 CFU mL-1, 107 cfu mL-1, 109 cfu mL-1, and 1011 cfu mL-1.  The third factor was N-fertilizer dosages which consisted of 50% of plant nitrogen necessity (equivalent to 57.50 kg N ha-1), 75% of plant nitrogen necessity (equivalent to 86.25 kg N ha-1), and 100 % of plant N necessity (equivalent to 115 kg N ha-1).  The research showed that GPEBC of the Consortium B had a better effect on rice yiels than Consortium A.  The population density of 107 cfu mL-1 of GPEBC increased the growth and the yield of rice grown on swamp soil. Treatment combination of 75% of plant N necessity, and 107 cfu mL-1 of population density produced the best production of Consortium B  (GPEBC) for rice grown on swamp soil.